Sistem Pendukung Keputusan Pemilihan Susu Formula pada Balita Menggunakan Metode Simple Additive Weighting (SAW) - Dwi Fitri Rahayu; Elisa Br Sembiring; Harninda Br Keliat; Safrizal Safrizal (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2025)
Formula milk is packed with essential nutrients. It contains beneficial components such as carbohydrates, proteins, fats, vitamins, sodium, DHA, and more. High-quality formula milk should not lead to gastrointestinal issues such as diarrhea, vomiting, or problems with digestion, nor should it cause coughing, breathing difficulties, or skin reactions due to an incorrect formula choice. This research aims to explore how mothers select suitable formula milk for their babies. The study utilizes the SIMPLE ADDITIVE WEIGHTING (SAW) method to determine alternative options based on pre-assigned weights and criteria. Following this, the ranking method is applied to identify the best alternative. According to the findings, five alternatives were evaluated: MORINAGA CHIL KID, LACTOGEN, SGM, BEBELOVE, and NUTRIBABY ROYAL 1. Additionally, five criteria were considered: Milk Price, Safety (Bpom Certification, Halal, etc.), Nutritional Content (Protein, Calcium, Iron, Vitamins, etc.), Taste (Natural Sweetness, Vanilla, Honey), and Market Availability.